No audience left behind, one App fits all: an integrated approach to accessibility services - Estella Oncins; Pilar Orero (JoSTrans: The Journal of Specialised Translation)
Most academic research on Audiovisual Translation and specifically on Media Accessibility has focused on content creation. If media content today can be compared to the visible tip of the iceberg, technology represents the unknown hidden part. Accessibility services are epigonic to media content, presenting an intimate relationship between technology for delivery and technology for consumption. Technology allows not only for the production of media content and access services, but also elicits new formats and interactions. This paper focuses on accessibility services delivery. The first part provides a brief on state-of-the-art accessibility apps available in the market today, including emerging trends and market uptake. Section 2 presents audience needs away from the classical medical classification of assistive technologies and an analysis of existing accessibility apps. Section 3 presents a novel solution that is currently available in the market for transmedia storytelling. The new app has been designed to provide personalised access, away from one-size-fits-all services.